Preparation of non-uniform gradient structures on the basis of Ge₄₀S₆₀ alloys with modifiers - Loya, V.Yu.; Lada, A.V.; Krafchyk, S.S.; Puga, P.P.; Puga, H.D. (Functional Materials, 2005)
А comprehensive thermographic study of Ge₄₀S₆₀ combinations with modifiers (Рb, AI, Bi and Тe) has been carried out. It has been shown that under heating, the modifier interacts with the Ge₄₀S₆₀ alloy occurs forming new compounds, i.e. Ge₄₀S₆₀-modifier ones. The technological conditions of the production of non-uniform gradient thin-film structures have been developed and the transmission and reflection spectra of those structures have been investigated. The dispersion of the refractive indices of thin-film gradient structures in the transparency region has been studied. Проведены термографические комплексные исследования системы Ge₄₀S₆₀ c модификаторaми (Рb, AI, Bi и Тe). Показано, что при нагревании происходит взаимодействие модификаторов и сплава Ge₄₀S₆₀ с образованием новых соединений Ge₄₀S₆₀-модификаторы. Разработаны технологические условия получения неоднородных градиентных тонкопленочных структур, исследованы их спектры пропускания и отражения. В области прозрачности исследована дисперсия показателей преломления полученных тонкопленочных градиентных структур. Проведено термографiчнi комплекснi дослiдження системи Ge₄₀S₆₀-модифiкатори (РЬ, AI, Bi i Тe). Показано, що при їх нагрiваннi проходить взаємодiя модифiкаторiв iз
сплавом Ge₄₀S₆₀ з утворенням нових сполук Ge₄₀S₆₀-модифiкатори. Розроблено технологiчнi умови одержання неоднорiдних градiєнтних тонкоплiвкових структур та дослiджено їхнi спектри пропускання i вiдбивання. В областi прозоростi дослiджено дисперсiю показникiв заломлення одержаних тонкоплiвкових градiєнтних структур.